Contribuição para o aumento da confiabilidade na entrega de pacotes em redes de sensores sem fio multissaltos - Godoi, Fabrício Negrisolo de (2018)
Wireless Sensor Networks are being used to collect a large amount of data from the most diverse environments and forward it to data collectors, which are also responsible to analyze such data for a particular purpose. However, these networks rely on unreliable communication medium that is susceptible to noise and interference, which results in loss of the packages that are being transported in the routes from the sensors to the data aggregators. In addition, the devices used in these networks have restrictions on their processing, storage, and communication capacity, which diminishes, even more, the reliability of the data delivery, since it becomes impracticable to use complex methods for error correction, or even to use appropriately sized network buffers. Therefore, this work describes a new communication method named μNet, which aims to increase the delivery rate of packets in multi-hop networks. Such approach is based on hop-by-hop control messages to ensure that the packet has been properly forwarded. Besides that, the μNet is designed to be compatible with constrained devices, reducing the size of headers of the protocols and the size of the network buffer. Using simulations tools to compare the μNet with widely used WSNs protocols, it is demonstrated that this approach results in better end-to-end reliability in networks susceptible to interference.